2016
DOI: 10.1097/jpn.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media by Fathers of Premature Infants

Abstract: Although parents of premature infants experience many challenges when transitioning home from the neonatal intensive care unit, healthcare providers and social support systems tend to focus on mothers and infants rather than fathers. Unfortunately, very little is known about paternal concerns and needs as compared with maternal ones. The lack of understanding about paternal needs may lead to inadequate designs of neonatal intensive care unit family support programs with less involved fathers, all of which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…Similarly, another study queried families about what content they would share on social media and 79% answered that they would be interested in joining a "native-language online networking site providing: (1) general information on prematurity, (2) explanations of abbreviations commonly used in a hospital setting, and (3) details of common medical problems and the treatment thereof, including the availability of local therapists and follow-up services" [53]. Social media might be particularly useful for fathers as a platform to discuss their concerns and gain emotional support in future studies [54]. It also might be useful for families with CMC to also have similar supports for family members.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study queried families about what content they would share on social media and 79% answered that they would be interested in joining a "native-language online networking site providing: (1) general information on prematurity, (2) explanations of abbreviations commonly used in a hospital setting, and (3) details of common medical problems and the treatment thereof, including the availability of local therapists and follow-up services" [53]. Social media might be particularly useful for fathers as a platform to discuss their concerns and gain emotional support in future studies [54]. It also might be useful for families with CMC to also have similar supports for family members.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers were most commonly parents (n = 19, 61%) [ 30 , 31 , 33 , 35 38 , 41 44 , 47 49 , 51 , 52 ] and unspecified family caregivers more broadly—which could include parents, but the term was more broadly defined (n = 7, 23%) [ 23 , 24 , 26 , 27 , 32 , 39 , 50 ]. One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ]. Few studies reported additional perspectives from members of the clinical care team (e.g., nurses, primary care physicians) (n = 3, 10%) [ 29 , 34 , 50 ] or critical care patients (n = 3, 10%) [ 22 , 28 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because of this, and the overall lack of health professional and social support for fathers of preterm infants, new strategies are urgently needed to improve the access to quality support for fathers of preterm infants. 18,19 Hospital-based interventions to reduce stress and support for parents of preterm infants during the neonatal period can improve post-discharge outcomes for parents and infants. [20][21][22][23][24] Contextual factors are also important to consider, including the amount and quality of family or healthcare provider support.…”
Section: Discussionmentioning
confidence: 99%